2021
DOI: 10.1002/ehf2.13594
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience covering 50 consecutive cases of large Impella implantation at a single heart centre

Abstract: Aims Pre‐operative or post‐operative heart failure (HF) and cardiogenic shock of various natures frequently remain refractory to conservative treatment and require mechanical circulatory support. We report our clinical experience with large Impella systems (5.0 or 5.5; i.e. Impella 5+) (Abiomed Inc., Boston, USA) and evaluate the parameters that determined patient outcome. Methods and results The initial 50 cases of Impella 5+ implanted for acute HF between November 2018 and August 2020 at a single centre were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…From 4173 articles, we reviewed 206 full-text articles. In total, we included 71 studies (63 observational, 8 PSM/RCTs) detailing 4280 adult patients that reported on the use of microaxial LVADs in CS ( Figure 1 ) [ 16 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 …”
Section: Resultsmentioning
confidence: 99%
“…From 4173 articles, we reviewed 206 full-text articles. In total, we included 71 studies (63 observational, 8 PSM/RCTs) detailing 4280 adult patients that reported on the use of microaxial LVADs in CS ( Figure 1 ) [ 16 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 …”
Section: Resultsmentioning
confidence: 99%
“…From November 2018 to October 2021, 100 consecutive Impella 5+ ( n = 96 for Impella 5.0; n = 4 for Impella 5.5) were implanted to treat acute CS in 90 cases (i.e., episodes of care) at a single institution. We previously reported our very initial experience with Impella 5+ in the first 50 consecutive cases treated at our center between November 2018 and August 2020 9 . In this current study, we have now added more patients to clarify the stated hypothesis and the purpose of this study.…”
Section: Methodsmentioning
confidence: 78%
“…Postoperative management after Impella 5+ follows as we described before ( 9 , 10 ). Briefly, all parameters displayed in Impella monitor, e.g., Impella setting, Impella flow, purge pressure, purge flow rate, and placement signal, were documented every 3 h. All patients underwent chest X-ray evaluation every day to examine the position of the Impella pump.…”
Section: Methodsmentioning
confidence: 99%